Mental health and bioethics: a symbiotic relationship - Frontera Roura, Ernesto A. (Acta Bioethica, 2009)
The purpose of this paper is to reflect about the strong relationship, of mutual nurturance if you will, seen about issues related to mental health and illness, psychiatry, bioethics and public health. An attempt is made to describe and explain the scope of each concept; to incorporate epidemiological data that facilitate us to appreciate the magnitude of the problem of mental health around the planet; to justify the need to attend the situation with the organization and operation of a mental healthcare system of services that respond to certain ethical parameters; and identify some areas in which bioethics is an essential element in the analysis of the problem and in establishing the basis of the solution.